Antibacterial Activity of Isolates from Digestive Tract of Catfish (Clarias gariepinus) As Probiotic Candidates At PT. Biotech Cipta Kreasi - Toto Apriliyanto; Nosa Septiana Anindita; Wisnu Adhi Susila (International Journal of Health Science and Technology, 2021)
African catfish (Clarias gariepinus) is a popular fish in the community because it provides a high level of protein at a low cost. The motile aeromonas septicemia (MAS) disease produced by Aeromonas hydrophila (A. hydrophila) infection is one of the things that create difficulties in the cultivation of this fish. Synthetic antibiotics are commonly used in MAS disease control management efforts in fish farming, which have have an influence not only on fish but also on consumers. The application of probiotic Bacillus sp isolated from the digestive tract of catfish as a means of preventing the sickness is one option. Enzymatic tests (lipolytic, amylolytic, cellulolytic, proteolytic activity) and antagonist testing were used to assess the probiotic activity of the Bacillus sp isolates.